Analysis of Public Services Quality of Service Unit AK.1 (Yellow Card) at Dinas Tenaga Kerja dan Transmigrasi Kota Semarang - Baidi Abdullah; Endang Larasati Setyaningsih; Tri Yuniningsih (Journal of Public Policy and Management Review, 2012)
Functions of public service is one of the fundamental functions it must fulfill the government both at central and regional levels. Given the government's main function is to serve the community, the government needs to continue to work to improve the quality of service. One is the service AK.1 (Kartu Kuning) in Dinas Tenaga Kerja dan Transmigrasi Kota Semarang. This study aims to determine the effect of employee job skills and motivation to quality of service AK.1 (Kartu Kuning) in Dinas Tenaga Kerja dan Transmigrasi Kota Semarang.This study uses the type of explanatory variables to test the relationship between the researched. And measure how much influence the relationship of independent variables and the dependent variable. The results showed that there was a positive relationship between employee job skills and motivation to the quality of service, so that the initial hypothesis is accepted. The results showed that job skills of the variables (X1) and motivation variables (X2) has a positive relationship with service quality variables (Y) in Dinas Tenaga Kerja dan Tranmigrasi Kota Semarang . In accordance with the provisions of the statistical test, it can be concluded that Ho refused and Ha is received significantly, with KD = 98.2%.